Cure for What Ails You: Advertising and Labeling of Patent Medicine Before and After 1906 - Yokes, Hayden (My University, 2017)
The American Western frontier was a dangerous place full of hazards people desperately needed to counter, and rather than turning to physicians they did not trust, they utilized patent medicine. These remedies were used across the United States, and they were promised to perform miracles for those who relied on them. As criticism of the industry increased, the government passed a series of laws controlling the manufacturing, labeling, and advertising of these drugs. This legislation eventually led to the highly controlled market in the United States today, and though these laws were intended to limit the sale of patent medicines, companies found ways to get around them and continue to sell their products. This paper is a case study of how one Wisconsin company was forced to adapt their labeling and advertising in order to operate within the confines of changing laws. This was something all companies selling patent medicines at the time had to do, and Willson Monarch Laboratory was not unlike others in their methods to survive in the better controlled market. They had to undergo drastic change to be able to keep selling their products, and the surviving records indicate the specific ways in which their labels changed.
Keywords: Willson Monarch Laboratory -- Wisconsin; Pharmacy -- History; Advertising -- Medicine; Patent medicines